(untitled) (CIPEEX, 2025)
In recent years, the use of orthodontic aligners has increased significantly, driven by technological advancements such as virtual planning software. These tools enable detailed planning of tooth movement, providing greater clinical precision. However, treatment success directly depends on the knowledge, attitudes, and practical experience of professionals using these technologies. The aim of this pilot study was to investigate the relationship between the use of these software programs and achieving results consistent with orthodontists’ treatment plans. Through a cross-sectional study, 14 orthodontists participated in an online questionnaire regarding their knowledge and practices with aligner planning software. Among respondents, 78.6% reported moderate difficulty handling the programs, and approximately 80% took more than 20 minutes to review and adjust a treatment plan. Additionally, 65.3% of professionals made at least four modifications to treatment plans before final approval. Regarding clinical outcomes, 64.28% stated that results frequently matched the initial plan. Despite the advantages of these technologies in increasing precision and confidence, challenges in efficiently using digital tools remain, affecting full implementation in clinical practice. The study highlights the importance of continuous training for orthodontists working with aligners to optimize outcomes and treatment predictability.